ANALISIS NILAI TAMBAH INDUSTRI KERIPIK TEMPE SKALA RUMAH TANGGA (Studi Kasus Desa Lerep Kecamatan Ungaran Barat Kabupaten Semarang) - Ulil Mar’atissholikhah; Darsono DarsonoDarsono; Eka Dewi Nurjayanti (MEDIAGRO, 2013)
The purposes of this research are to know the value added of households scale tempe chips industries, to know the risks of tempe chips business in the Lerep Village and to know the feasibility analysis of households scale tempe chips industries. The research area sampling method is purposive in the Lerep Village West Ungaran District Semarang Regency, that is one of home industries centre of tempe chips. The analysis methods used in this research use value added analysis of Hayami’s method (1987), analysis of business risks and the analysis of feasibility using BEP and R/Cratio. Based on the research results, the amount of value added from tempe chips industries is Rp 38,452.99/kg with a ratio of 82.34 percent. Margin obtained is Rp 40,728.24 which distributed to each of the factors (labor income 12.22 percent, contribution of other input 5.59 percent and industry profits 82.19 percent). Industries of tempe chips has the variation coefficient value (CV) more than 0.5 that is equal to 2.92 and lower limit value gains (L) is Rp 158,012.18, so that industry of tempe chips business risk with the possibility of loss is Rp 158,012.18. The total cost of the production process tempe chips Rp 347,006.09 and the production volume value BEP 0.067 kg tempe chips and BEP value revenue Rp 1,827.9. While the R/C ratio value is 1.54 so that, the tempe chips industries business is feasible because the R/Cratio value is more than 1 (one). The suggestion to businessman is hoped to develop their business by increasing the number of output products of tempe chips and to the government can give more attentionin the form of management training and others.   Key word: value added, tempe chips industries, business risk, feasibility analysis